Historiographie de préhistoriens et de protohistoriens français du XX siècle : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). - Djindjian, François (UISPP proceedings series, 2021)
In France, the post-World War II period corresponds to a second golden age of prehistory and protohistory, thanks to the development of the CNRS and the creation of the first university chairs. This volume presents the biographies of a wide selection of French archaeologists whose scientific work has particularly marked this period.